The Application of the AHP-TOPSIS Method for a Decision Support System in Determining the Areas for Enforcement of Restrictions on Community Activities at the District Level in West Java - Hutabarat, Jan Joy Jeferson; Sihotang, Jay Idoan (8ISC Proceedings: Covid-19, 2022)
Currently, the world has been hit by an outbreak of a virus called Covid-19, commonly called Coronavirus. Until now, the coronavirus is quite deadly, which causes severe symptoms to death for sufferers. Because the high number of deaths and positive patients requires countries to make policies to stop the spread of Covid19, each country has different policies. One of the policies of the Indonesian government is called the Implementation of Community Activity Restrictions (PPKM) which means limiting activities in a certain area that has the highest cases. To determine a PPKM area is not easy due to several factors. A Decision Support System (DSS) is a computer-based system that produces various alternatives for making decisions. The method used is the Analytic Hierarchy Process (AHP) and Technique for Others Preference by Similarity to Ideal Solution (TOPSIS); the AHP method is used for automatic weighting for each criterion to be used and reduces subjective weighting. In comparison, TOPSIS performs ranking by optimizing positive ideal solutions and negative ideal solutions. The conclusion of this research is that it can help the government to make decisions in the implementation of the Enforcement of Restrictions on Community Activities. Keywords : Decision Support System, PPKM, AHP, TOPSIS